Harlequin Ichthyosis: A Fatal Disease - Rahman, Zainab; Dev, Archana; Ahmed, Tofayel; Sultana, Rabaka; Paul, Joyoshree; Rahman, Nahidur (Jalalabad Medical Journal, 2025)
Harlequin ichthyosis (HI) is a rare and severe form of congenital ichthyosis that is inherited in an autosomal recessive manner. Affected newborns are frequently premature, and this illness may be fatal at birth. Severe hyperkeratosis, widespread fissuring, and varying degrees of cutaneous abnormalities are the disease's hallmarks. Here a case of a harlequin baby is reported who was born prematurely and to consanguineous parents. She had typical manifestations of harlequin ichthyosis. Conservative treatment was given, but the baby died on the eighth day of her life. Jalalabad Med J 2022; 19 (2): 67-70